Effects of stiffener area in composite steel-concrete beam with web opening: numerical, experimental and theoretical investigation - Mastan, Sheik; Sekar, Anandh; S., Sindhu Nachiar (Frontiers in Materials, 2025)
Generally, the Openings in composite steel-concrete beams (CBs) for conduits and pipelines often compromise their flexural capacity. To mitigate this, longitudinal stiffeners (LS) and transverse stiffeners (TS) are strategically placed near the web openings. While previous research has explored various opening shapes and stiffener placements, limited studies have examined the impact of stiffener area on flexural performance. This study investigates the influence of stiffener area on the bending performance of composite beams with openings (CBOs). Numerical analysis using ABAQUS (v6.14) was conducted on beams with circular (CBC), rectangular (CBR), and triangular (CBT) openings, varying the breadth of stiffener (b) of LS and TS as 4 mm, 6 mm, 8 mm, and 10 mm. Results indicate that the ultimate load-carrying capacity of CBC with LS and TS increased from 290.50 kN (without stiffeners) to 375.56 kN, 383.46 kN, 387.42 kN, and 400.00 kN as the stiffener breadths were increased to 4 mm, 6 mm, 8 mm, and 10 mm, respectively, finally achieving a 37.6% improvement and comparable to 401.70 kN capacity of a beam without openings (CB). For CBR and CBT with the maximum breath of stiffener, the load-carrying capacities were 37% (380.50 kN) and 73% (336.86 kN) greater, respectively, compared to CBR and CBT without stiffeners. Thus, numerical results indicate that with an increase in the area of both stiffeners, the beam with openings exhibits an ultimate bearing capacity comparable to a beam without web openings. Further experimental investigation was performed on three specimens scaled down at a ratio of 1:0.32; here, the load-bearing capacity of the CBC with both stiffeners of the breath of 10 mm is 156.40 kN, which is 44% greater than the scaled-down CBC of 108.80 kN and comparable to the scaled-down CB’s capacity of 151.12 kN. These experimental and numerical results emphasise that combining LS and TS with the maximum area of stiffeners, i.e., l × b (b = 10 mm), is most effective in maintaining the stability and load capacity of CBOs. Finally, the numerical and experimental results are validated against the theoretical results.